Investigating the Underlying Factors and Outcomes of the Madheshi People's Movement in Nepal (2007-2008) - Pokharel, Arjun Prasad (Academia Research Journal, 2024)
The study focuses on the Madheshi People’s Movements in the Tarai region of Nepal during 2007 and 2008. The key issues investigated include the catalysts behind these movements, their influence on Nepalese politics, and the sustained implications for Madheshis and other marginalized communities. The primary aim of this research is to discern the causes of the Madheshi People’s Movements, understand their impact on Nepalese politics, and evaluate the lasting effects of the achievements stemming from these uprisings. Utilizing semi-structured interviews, Focus Group Discussions (FGD), questionnaire surveys, and an extensive review of secondary data, the research unfolds the transformative nature of the Madheshi People’s Movement of 2007. The methods employed provide a comprehensive understanding of the socio-political landscape surrounding these movements. The research identifies three core elements contributing to the initiation of the 2007 and 2008 Movements: perceived discrimination against Madheshis, radicalization of regional and ethnic issues influenced by the Maoist rebellion, and the precedent set by the People’s Movement of 2006. The Madheshi People’s Movements significantly impacted Nepalese politics, leading to the declaration of Nepal as a federal state and notable electoral success for Madheshi political parties. However, internal divisions emerged within the Madheshi identity, with marginalized communities distancing themselves from the Madheshi label, posing a potential threat to the movements' achievements. While the Madheshi People’s Movements brought about crucial changes in Nepal's political landscape, the emergence of internal dissent among Madheshis calls for a strategic repositioning of Madheshi political parties. To preserve their achievements, these parties must transcend identity boundaries and represent the interests of all marginalized communities in Nepal. Failure to do so risks eroding the gains made through the identity politics initiated by the Madheshi parties.